2015
DOI: 10.1061/(asce)ee.1943-7870.0000959
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Maintenance of Floating Treatment Wetlands for Urban Stormwater Management

Abstract: WOS:000363088600005International audienceThe floating treatment wetland (FTW) is an innovative hydroponic device which can be installed on the surface of a stormwater retention pond to improve its pollutant removal efficiency. Limited full-scale experiments have been published, and no design or maintenance guidelines have been developed to date to promote their use. This paper presents implementation and maintenance considerations developed based on the monitoring of three full-scale ponds retrofitted with FTW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…The highly variable results found in this study are likely to be a result of highly variable, and/or low concentration pollution inflows. This result has also been found in previous studies [19,20,22,23]. Results that were less than the limits of detection (LoD) for that particular test, have been shown as 50% of the LoD.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The highly variable results found in this study are likely to be a result of highly variable, and/or low concentration pollution inflows. This result has also been found in previous studies [19,20,22,23]. Results that were less than the limits of detection (LoD) for that particular test, have been shown as 50% of the LoD.…”
Section: Resultssupporting
confidence: 71%
“…Prior to statistical testing, concentrations of TSS, TN and TP were log transformed (Equation (4)) to achieve normality (Ryan-Joiner p > 0.01). A paired T-test was performed on the log-transformed data to calculate if the difference between means was significant [21,22].…”
Section: Performance Metricsmentioning
confidence: 99%
“…bypassing flows) experienced in other studies [10,18], impermeable polyvinyl chloride (PVC) curtains were installed along the sides of the FTWs that fanned out towards the lake banks ( Figure 2). These ensured all inflows from Inlets 1 and 2 were treated by the FTWs.…”
Section: Study Sitementioning
confidence: 99%
“…These studies have shown that FTW are effective at removing pollutants from both wastewater [12][13][14][15] and stormwater [7,16,17]. The number of field studies undertaken on FTWs is limited, particularly in the application of FTWs to stormwater treatment [3,18,19]. Smaller-scale field studies in the USA [19] and New Zealand [4] have shown FTWs to be effective in removing a variety of pollutants from stormwater runoff from highways.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies suggest strong potential for FTW use in stormwater systems, most studies have been performed in simulated environments such as mesocosms with relatively few studies taking place on real-world stormwater systems until recently [7,[23][24][25]. Because the performance of FTWs depends heavily on the design of the stormwater pond as well as characteristics of the FTW itself (i.e., surface area coverage and plant density) it is important to investigate real-world performance [14,23,24].…”
Section: Introductionmentioning
confidence: 99%